Profiles of Ethnic-Racial Identity, Socialization, and Model Minority Experiences: Associations with Well-Being Among Asian American Adolescents. - Xie, Mingjun; Fowle, Jillianne; Ip, Pak See; Haskin, Milou; Yip, Tiffany (Journal of Youth & Adolescence, 2021)
Ethnic-racial identity, ethnic-racial socialization, and racialized experiences are fundamental to the development of youth of color. However, most prior studies have examined their developmental impact in isolation. The present study fills this gap using a person-centered approach to elucidate patterns of ethnic-racial identity, socialization, and model minority experiences among 145 Asian American adolescents (M = 14.3, SD = 0.59; 65% female). Three distinct profiles were identified. Overall, adolescents with stronger ethnic-racial identity and more cultural socialization but less preparation for bias (Salient, 13%) demonstrated better psychosocial and academic outcomes. Adolescents with moderate levels on the six indicators of ethnic-racial identity, socialization, and model minority experiences (Moderate, 72%) reported better sleep quality and less delinquency. Adolescents with low levels of ethnic-racial identity and cultural socialization but greater preparation for bias (Marginal, 15%) had the least adaptative outcomes across all domains. The findings observed the heterogeneity of ethnic-racial experiences within the Asian American group and highlighted the importance of examining the combined influences of ethnic-racial identity, socialization, and model minority experiences on health and well-being among Asian American adolescents from a multidimensional perspective.